Mirogabalin - the use of a new gabapentinoid in the treatment of diabetic neuropathy and postherpetic neuropathy and other conditions - Weronika Gawel; Sylwia Zdun; Klaudia Walczak; Zuzanna Wesołowska; Przemysław Jędruszczak (Nicolaus Copernicus University in Toruń, 2023)
Introduction: Mirogabalin is a new drug from the gabapentinoid group first registered in Japan in 2019. It has found use in the treatment of peripheral neuropathic pain in diabetic neuropathy and postherpetic neuropathy. Purpose: In this article, we review studies on the efficacy and safety of mirogabalin in the treatment of registered indications and its potentially new applications. Materials and Methods: We reviewed the literature available in the PubMed database, using the key words: "mirogabalin", "neuropathy" "pregabalin". Results: Mirogabalin has been registered for the treatment of neuropathic pain in diabetic neuropathy and postherpetic neuropathy. The literature shows that it is effective and safe in the above-mentioned indications.  Its use has also been described: in the treatment of neuropathic pain of other etiologies with intolerance to pregabalin, as a coanalgesic in the treatment of pain in the course of cancer, and in neuropathy caused by chemotherapy. It has been shown to be effective in all of the aforementioned cases. Studies have shown no clinically significant effect of mirogabalin in the symptomatic treatment of fibromyalgia pain.  It has a good safety profile and a low number of adverse effects. Conclusions:. Mirogabalin is a drug that has the potential to improve the efficacy of treatment of neuropathic pain due to various causes.  There is a need to continue conducting studies on larger groups of patients in order to make wider use of its potential in clinical practice.